2012
DOI: 10.1521/jscp.2012.31.4.410
|View full text |Cite
|
Sign up to set email alerts
|

A Love That Doesn't Last: Pornography Consumption and Weakened Commitment to One's Romantic Partner

Abstract: we examined whether the consumption of pornography affects romantic relationships, with the expectation that higher levels of pornography consumption would correspond to weakened commitment in young adult romantic relationships. Study 1 (n = 367) found that higher pornography consumption was related to lower commitment, and Study 2 (n = 34) replicated this finding using observational data. Study 3 (n = 20) participants were randomly assigned to either refrain from viewing pornography or to a self-control task.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(74 citation statements)
references
References 48 publications
5
66
0
3
Order By: Relevance
“…Couples need to be able to define infidelity before they can establish clear rules about Internet use [49]. Therapists need to consider the importance of the Internet in romantic relationships, and should be aware of the possible behaviors that might predict infidelity, such as pornography use [84]. Online behaviors should be assessed on a continuum, ranging from simple online entertainment, to online dating, to cyber addiction [53].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Couples need to be able to define infidelity before they can establish clear rules about Internet use [49]. Therapists need to consider the importance of the Internet in romantic relationships, and should be aware of the possible behaviors that might predict infidelity, such as pornography use [84]. Online behaviors should be assessed on a continuum, ranging from simple online entertainment, to online dating, to cyber addiction [53].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…A 2012 study found that when half of participants tried to abstain from pornography use for 3 weeks, they reported higher levels of relationship commitment (Lambert, Negash, Stillman, Olmstead, & Fincham, 2012). These two studies demonstrate that even in those who are not addicted, who only endeavor to abstain, and who do so for a mere 3 weeks, changes are significant.…”
Section: What Does Research That Removes Ip Use Find?mentioning
confidence: 96%
“…Similarly, pornography is another evolutionary novel factor that may have an effect on men's sexual functioning. For example, excessive porn consumption reduces romantic relationship satisfaction (Lambert et al 2012), and it is linked with greater endorsement of, and more frequent participation in, extra-marital relations (Wright 2013). In addition, other evolutionary novel environmental conditions such as air pollution, high levels of stress, unemployment, and overpopulation may likewise negatively affect sexual functioning.…”
Section: Predictions and Evidencementioning
confidence: 99%